SELF CARE TRADITIONAL HERBAL THERAPY FOR PSORIASIS (AYUSHDHARA, 2020)
Background:  Psoriasis a skin ailment leading to frustration, stress and social isolation is a vital health problem to be addressed. Research in the area of herbal medicine and rejuvenation practice is based on the number of Random trials in the prevalence of a disease and a survey on the number of published in the journals indexed in the subject area.Objective: To document successful casestudies and suggest the progressive herbal treatment plan carried out in Rajendra Herbal Research and training centre.Methodology:In a survey of 1000 patients with reported skin problems undergoing traditional herbal and Ayurvedic treatment, 554 had scratchy itch related skin problems, 215 bite based blisters, 32 Hair related Allopecia, 47 White patch, 36 Black patch, 49 psoriasis and 67 patients had red rashes. The group had 518 males and 482 females. Five sets of skin patients were chosen for a cohort study with 0 to 70 years of age having151, 149, 149,154 &175nos.An experiment was designed to carryout a randomized double blind placebo controlled study in 140 psoriatic patients.Results: Random survey of 1000 skin patients and cohort study of five sets of herbal respondents of agegroup 0-70 were tabulated.Out of the 140 treated Psoriatics, sixcase studies presented with the treatment plan followed at the Rajendra Herbal Research centresshowedsuccesstowards positive health.Conclusion:In all the sets females out-numbered males with the prevalence of skin problems in 11 to 40 years of age. More females of the age group 41 to 50 ended up in Psoriatic arthritis and males with Diabetes. Rajendra supportive herbal therapy for Psoriasis promises social freedom and psychological harmony.